An eventful year for Umno survivability: General assembly set to further unite the party's rank and file - Ariff, Syed Umar (New Straits Times, 2013)
AMUSINGLY, some analysts are at loss to deduce issues that may take centre stage in the upcoming Umno general assembly next week.A host of issues were resolved through a barrage of events taking place throughout the year; from the prolonged 13th General Election campaign to the recently-concluded party polls, which saw more than 146,000 delegates vote to preserve Umno's current leadership lineup